2002
DOI: 10.1128/iai.70.11.6389-6398.2002
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Variation within the Alanine-Rich Repetitive Domain of Streptococcal Antigen I/II

Abstract: Members of the antigen I/II family of cell surface proteins are highly conserved, multifunctional adhesins that mediate interactions of oral streptococci with other oral bacteria, with cell matrix proteins (e.g., type I collagen), and with salivary glycoproteins, e.g., gp340. The interaction of gp340 (formerly designated salivary agglutinin) with Streptococcus mutans requires an alanine-rich repetitive domain (A region) of antigen I/II that is highly conserved in all members of this family of proteins. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…In addition, salivary agglutinin is known for its S. mutans-agglutinating properties (37), while AgI/II, SspB, and SspA bind to 300-to 400-kDa salivary agglutinin (5,8,9,37). In the present study, the binding receptor of the SspB peptide was demonstrated to be a salivary component with a high-molecular-weight complex.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, salivary agglutinin is known for its S. mutans-agglutinating properties (37), while AgI/II, SspB, and SspA bind to 300-to 400-kDa salivary agglutinin (5,8,9,37). In the present study, the binding receptor of the SspB peptide was demonstrated to be a salivary component with a high-molecular-weight complex.…”
Section: Discussionmentioning
confidence: 78%
“…The A regions of PAc and PAg are thought to assume an ␣-helical structure (5,32,44). Recently, new experimental evidence has shown that A regions from the binding proteins (SspA and SpaP) of S. gordonii and S. mutans that bind to salivary components are highly stable and ␣-helical (8). However, the A region of SspB is less stable than the corresponding A regions of SspA and SpaP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we hypothesize that the PP II-like helix of the proline-rich region interacts with the alanine-rich region, which itself is predicted to adopt an ␣-helical structure (5,(33)(34)(35). The interaction of PP II-like helices with ␣-helices has been described before for turkey pancreatic polypeptide, a 36-amino acid hormone (28,36), where residues 2 to 8 form a PP II-like helix that is closely packed against an ␣-helix formed from residues 14 -32.…”
Section: Discussionmentioning
confidence: 99%
“…SpaP is a multi-functional adhesin, facilitating binding of the bacteria to components of the enamel pellicle (Curtiss, 1985;Lee et al, 1989), as well as to collagen and other host proteins (Demuth and Irvine, 2002;Love et al, 1997). Mutants lacking SpaP showed an impaired capacity to attach to salivacoated hydroxylapatite.…”
Section: Lemos Et Almentioning
confidence: 99%